A comparative study for shear testing of thermoplastic-based composites and metal-composite hybrids. (October 2020) - Zinnecker, V.; Stokes-Griffin, C.M.; Khudiakova, A.; Wolfahrt, M.; Compston, P.
Abstract: This study presents the novel application of the compression shear test (CST) for characterising bonding strength of metal-composite hybrids made of steel and carbon fibre/polyamide 6 (CF/PA 6). An automated laser-assisted tape placement (ATP) process was used to lay-up the CF/PA 6 tapes on laser textured steel substrates. CST is of interest due to the ease of sample manufacturing as a relatively small test specimen is required. The results were compared with standardised single lap shear tests (ASTM D3165), which requires manufacturing of a double-notched test specimen. For benchmarking purposes, the compression shear test was also used to characterise the interlaminar shear strength of a plain CF/PA 6 composite. The results showed equivalent shear strength and similar failure modes for both tests of the metal-composite hybrid specimens. Grooved texturing of the steel substrate in the hybrid specimens promoted a mixed-mode (cohesive and adhesive) failure and a higher shear strength than for the composite-only specimens. Overall, the results showed that the compression shear test is a valid and efficient method to characterise the bonding strength of metal-composite hybrids and composites.